Confusional arousals during non-rapid eye movement sleep: evidence from intracerebral recordings. Issue 10 (16th July 2018) - Flamand, Mathilde; Boudet, Samuel; Lopes, Renaud; Vignal, Jean-Pierre; Reyns, Nicolas; Charley-Monaca, Christelle; Peter-Derex, Laure; Szurhaj, William
Abstract: Study Objectives: Confusional arousals (CA) are characterized by the association of behavioral awakening with persistent slow-wave electroencephalographic (EEG) activity during non-rapid eye movement (NREM) sleep—suggesting that sensorimotor areas are "awake" while non-sensorimotor areas are still "asleep." In the present work, we aimed to study the precise temporo-spatial dynamics of EEG changes in cortical areas during CA using intracerebral recordings. Methods: Nineteen episodes of CA were selected in five drug-resistant epileptic patients suffering incidentally from arousal disorders. Spectral power of EEG signal recorded in 30 non-lesioned, non-epileptogenic cortical areas and thalamus was compared between CA and baseline slow-wave sleep. Results: Clear sequential modifications in EEG activity were observed in almost all studied areas. In the last few seconds before behavior onset, an increase in delta activity occurred predominantly in frontal regions. Behavioral arousal was associated with an increase of signal power in the whole studied frequency band in the frontal lobes, cingulate cortex, insular cortex, and precuneus. Afterwards, a diffuse cessation of very low frequencies (<1 Hz) occurred. Simultaneously, a hypersynchronous delta activity (HSDA) (1–1.5 Hz) arose in a broad network involving medial and lateral frontoparietal cortices, whereas higher frequency activities increased in sensorimotor, orbitofrontal, and temporal lateral cortices. This HSDA was predominantly observed in the inferior frontal gyrus. Conclusions: During CA, the level of activity changed in almost all the studied areas. The embedding of a broad frontoparietal network, especially the inferior frontal gyrus, in an HSDA might explain the participants' altered state of consciousness.